FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KLIEN KANTOR AKUNTAN PUBLIK (STUDI EMPIRIS PADA 25 PERUSAHAAN DI PEKANBARU) - Charlie Tambunan; Andreas Andreas; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to find out influence of competence of audit team, independence, auditor change, and reputation of CPA Firm on client satisfaction. The population in this study are manager of accounting, staff of accounting and internal auditor whose working at company in Pekanbaru that use the services of a CPA Firm. This study is using survey method. Total respondents which is used in this study are 44 responden (58,7%). The analyzing method is Multiple Regression methods using SPSS (Stastical Product and Service Solutions) version 17. Result of this study indicates competence of audit team, independence, auditor change, and reputation of CPA firm influence to client satisfaction. The coefficient of determination in this study were 94,1 %. The four independent variables jointly influence dependent variable as much as 94,1 %, while 5,9% is influenced by other unclear variables.Keywords : Competence of Audit Team, Independence, Auditor Change, and Reputation of CPA Firm , Client Satisfaction.